Combination of in silico and molecular techniques for discrimination and virulence characterization of marine Brucella ceti and Brucella pinnipedialis - Girault, Guillaume; Freddi, Luca; Jay, Maryne; Perrot, Ludivine; Dremeau, Alexandre; Drapeau, Antoine; Delannoy, Sabine; Fach, Patrick; Ferreira Vicente, Acacia; Mick, Virginie; Ponsart, Claire; Djokic, Vitomir (Frontiers in Microbiology, 2024)
Introduction Mammals are the main hosts for Brucella sp., agents of worldwide zoonosis. Marine cetaceans and pinnipeds can be infected by Brucella ceti and B. pinnipedialis, respectively. Besides classical bacteriological typing, molecular approaches such as MLVA, MLSA, and whole-genome sequencing (WGS) can differentiate these species but are cumbersome to perform. Methods We compared the DNA and genome sequences of 12 strains isolated from nine marine mammals, with highly zoonotic B. melitensis, B. abortus, and B. suis, and the publicly available genomes of B. ceti and B. pinnipedialis. In silico pipelines were used to detect the antimicrobial resistance (AMR), plasmid, and virulence genes (VGs) by screening six open-source and one home-made library. Results and discussion Our results show that easier-to-use HRM-PCR, Bruce-ladder, and Suis-ladder can separate marine Brucella sp., and the results are fully concordant with other molecular methods, such as WGS. However, the restriction fragment length polymorphism (RFLP) method cannot discriminate between B. pinnipedialis and B. ceti B1-94-like isolates. MLVA-16 results divided the investigated strains into three clades according to their preferred host, which was confirmed in WGS. In silico analysis did not find any AMR and plasmid genes, suggesting antimicrobial susceptibility of marine Brucella, while the presence of the VGs btpA gene was variable dependent on the clade. Conclusion The HRM-PCR and Suis-ladder are quick, easy, and cost-effective methods to identify marine Brucella sp. Moreover, in silico genome analyses can give useful insights into the genetic virulence and pathogenicity potential of marine Brucella strains.